Enhanced Proinflammatory Cytokine Production and Immunometabolic Impairment of NK Cells Exposed to Mycobacterium tuberculosis and Cigarette Smoke - Rao, Yafei; Gai, Xiaoyan; Le, Yanqing; Xiong, Jing; Liu, Yujia; Zhang, Xueyang; Wang, Jundong; Cao, Wenli; Sun, Yongchang (Frontiers in Cellular and Infection Microbiology, 2022)
Smoker COPD patients with chest radiological signs of prior tuberculosis (TB) showed more severe lung damage, but the underlying mechanisms remain to be elucidated. Herein, we found that blood NK cells in smoker patients with active pulmonary TB (CS+ PTB group) showed altered proportion of subpopulations and excessive pro-inflammatory cytokine expression. In vitro experiments demonstrated that cigarette smoke extract (CSE) and PPD co-exposed NK-92 cells displayed enhanced pro-inflammatory cytokine production, decreased glycolytic influx and oxidative phosphorylation. These novel data highlight the potential roles of NK cells in the pathogenesis of tuberculosis-associated COPD.